A thousand words about the cardiopulmonary exercise test in respiratory system diseases - Jacek Tarchalski; Tomasz Piorunek; Przemysław Guzik (Journal of Medical Science, 2019)
The cardiopulmonary exercise test (CPET) is designed to measure some physiological variables related to the function of the cardiovascular and respiratory systems during exercise. Usually, the CPET is performed either on a treadmill or a cycle ergometer. In this mini‑review, we describe a set of parameters which are most commonly used to quantify CPET. We also summarize clinical indications for this test and interpretation of the obtained results in patients with respiratory system diseases. The CPET, if made appropriately, may deliver valuable information helpful in the diagnosis, e.g., of unexplained dyspnea, and prognosis, e.g., in chronic obturatory pulmonary disease, pulmonary hypertension, or interstitial lung diseases.